Pengaruh Model Pembelajaran Blended Learning Terhadap Hasil Belajar Siswa pada Materi Sistem Gerak Manusia di Kelas XI SMAN 2 Perbaungan - Nanda Sholeha; Indayana FebrianiTanjung; Reflina (Mu'allim, 2023)
The justification for this exploration is to see the effect of mixed learning on the learning outcomes of motion structures. Tests are used in this exam strategy. This study used a semi-trial research design. Participants from the following two classes were selected through total sampling in this study: 35 students from XI IPA 2 as the control group, with 34 students from XIIIPA 1 as the experimental group. Based on the examination and conversation, it was obtained that the t value was 4.309 > 1.689, so that H0 was rejected and Ha was declared. The hypothesis testing table also shows the level of significance: 0.000 0.05. Thus according to the justification for the items in the independent T test, it is quite well accepted that there is a difference in the usual learning outcomes of the posttest control group and the posttest exploratory encounter. Thus it can be concluded that the blended learning model influences the activities and learning outcomes of class XI students of SMA N 2 Perbaungan.